Evaluasi Aksesibilitas Sistem POLINDA Kabupaten Garut Berdasarkan Standar WCAG 2.2 - Akmala Akmala (Jurnal Algoritma, 2026)
The digitization of social services must be accessible to all citizens, including people with disabilities. This study evaluates the accessibility of POLINDA (Social Assistance Services of the Garut Regency Social Affairs Office) using WCAG 2.2 Levels A and AA. The subjects consist of a portal and four services based on Google Forms and Google Drive. The method adapts WCAG-EM as an initial evidence-based audit of 32 indicators under the principles of perceivable, operable, understandable, and robust. Indicators requiring DOM inspection, contrast testing, keyboard navigation, or screen reader testing—and which could not yet be verified—were assigned a “U” status. The results showed a verified indicator index of 78.6 percent: 19 met the criteria, six partially met the criteria, three did not meet the criteria, and four were not yet verified. The lowest score was in the “understandable” category (62.5 percent), influenced by mixed languages, Google authentication, inconsistent help, and cross-platform fragmentation. Priorities for improvement include access without login, language standardization, consistent help, labels and error messages, contrast and keyboard focus audits, and integration with the official portal. These results serve as a baseline that needs to be confirmed through technical audits and user testing.